Dietary Habits, Physical Activity and Sleep Pattern Among In-School Adolescents in Lagos, Nigeria - Akinola IJ; Odugbemi B; Bakare OQ; Odusote OA; Njokanma OF (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: Overnutrition has been documented at epidemic levels in children and adults. The associated risk factors may include poor dietary habits, sedentary behaviour, inadequate sleep and low parental education. Objective: To describe dietary habits, physical activity and sleep patterns among secondary school adolescents. Methods: A cross-sectional study of 1,120 adolescents recruited from public and private secondary schools in Lagos, Nigeria, was carried out to study the dietary habits, sleep patterns and physical activity in relation to nutritional status. Results: Ten per cent of the adolescents skipped breakfast, while 28% had fruits on up to five days of the week. Eleven per cent had a sweetened drink every day, while 20 % had a sweetened drink on most days of the week. One out of four (26%) adolescents had more than two hours of screen time daily, and only 5% engaged in sporting activities up to five times weekly. One-third of the students slept for less than six hours daily and experienced sleeping difficulties. Multivariate analysis showed that females were twice as likely not to participate in sports (OR = 2.38, CI = 1.3-4.37, p = 0.002 and to have a higher intake of confectionaries (OR = 1.47, CI = 1.07-2.04, p = 0.01. Conclusion: Poor dietary habits, inadequate physical activity and insufficient sleep were observed among secondary school adolescents. A multi-pronged approach to improve these behaviours is recommended.